P–212 Mitochondrial DNA content shows a significant association with timing of human embryo development and fertility diagnosis in euploid embryos. (6th August 2021) - Hur, C; Nanavaty, V; Chehab, A; Yao, M; Desai, N
Abstract: Study question: Does mitochondrial DNA content (mtDNA) correlate with clinical parameters and embryo morphokinetics using advanced time-lapse technology? Summary answer: mtDNA correlated with embryo morphokinetics and the growth trajectory of euploid embryos. Maternal age, anti-mullerian hormone level and fertility diagnosis were significantly associated with mtDNA. What is known already: With the push towards single embryo transfers, laboratories are working to improve embryo selection. In addition to conventional microscopy, preimplantation genetic testing and time-lapse microscopy have been utilized to aid in embryo selection. More recently, as mtDNA may represent the energy potential of an embryo, some data have supported the use of mtDNA as an additional tool. Limited studies have suggested that a lower amount of mtDNA is associated with higher rates of implantation and improved embryo quality. Study design, size, duration: This is a retrospective chart review. All embryos that underwent preimplantation genetic testing for aneuploidy (PGT-A) between January to December of 2020 were studied. Participants/materials, setting, methods: Women undergoing in vitro fertilization (IVF) with intracytoplasmic sperm injection undergoing PGT-A were studied. All patients were from a single academic institution. This study exclusively examined the characteristics of euploid embryos. Mitochondrial DNA content was expressed as a ratio of mtDNA:nDNA (MitoScore). Time-lapse imaging was utilized to evaluate embryo development every 15 minutes in 5–7 focal planes. Chi square test and Spearman correlation analysis were performed with a p-value of < 0.05 considered significant. Main results and the role of chance: A total of 494 embryos from 52 women who underwent 58 IVF cycles were cultured to blastocyst and 331 embryos were biopsied for PGT-A evaluation. Of these, 132 embryos were diagnosed as euploid. A moderate positive correlation was found between MitoScore and time to morula, time to blast and time to expanded blast (correlation value 0.54, 0.50 and 0.54, respectively; p < 0.001). Consistent with this trend, day 5 blastocysts had a significantly lower MitoScore values than day 6 blastocysts (20.2 v. 29.2; p < 0.001). When examining all biopsied euploid embryos, no significant association was found between MitoScore, blastocyst maturity, trophectoderm or inner cell mass scores. Our data also demonstrated a positive correlation between MitoScore and maternal age (correlation factor 0.33; p < 0.001). A negative association between MitoScore and serum anti-mullerian hormone levels (correlation factor –0.20; p < 0.021) was also noted. Of particular interest was the significant association between fertility diagnosis and mitochondrial score (p < 0.001). Even amongst euploid embryos, mtDNA content varied widely, potentially reflecting differences in embryo potential and quality. Additionally, the significant difference in MitoScore between that day 5 and day 6 blastocysts may reflect a fundamental difference in cytoplasmic characteristics and requires further study. Limitations, reasons for caution: Due to the study cohort of euploid embryos undergoing PGT-A, this study was biased for the selection of high grade embryos. This limited diversity in embryo quality may have masked other potential associations between mitochondrial content and blastocyst quality. Wider implications of the findings: mtDNA may be additional tool aiding in embryo selection as IVF labs work to improve pregnancy rates while minimizing the risks of transferring multiple embryos. To our knowledge, this is the largest study assessing the relationship of mtDNA content of blastocysts and the timing of embryo development using time-lapse imaging. Trial registration number: None